Effect of 3D‐woven glass fabric and nanoparticles incorporation on impact energy absorption of GLARE composites. Issue 10 (6th April 2017) - Amooyi Dizaji, R.; Yazdani, M.; Aligholizadeh, E.; Rashed, A.
Abstract : Proper combination of fiber reinforced composite and metal is a novel concept that it caused the advent of fiber‐metal laminates. This study reports the impact response of 3D‐woven glass fiber fabric composite cores experimentally, and it describes the effect of silica and graphene nanoparticles addition on energy absorption behavior of laminated fiber‐metal composites. The composites are manufactured by VARTM method with 71% fiber volume fraction. The low velocity impact tests are performed with drop‐weight impact test machine with various impact energies. The results show higher impact performance of plain‐weave samples compared with 3D‐woven glass fiber fabrics under different impact energies. The 3D‐woven glass fiber fabrics are preferred in case of using samples with lower weights. POLYM. COMPOS., 39:3528–3536, 2018. © 2017 Society of Plastics Engineers